Turkey Forest Policy Note - World Bank Group (World Bank, Washington, DC, 2017)
This Forest Policy Note, prepared by the World Bank, offers an outside view of the Turkish Forestry Sector, provides some strategic guidance to help define sector goals, and identifies opportunities for consideration in the continued development of the sector and for the implementation of the Turkish/World Bank Country Partnership Strategy which recognizes that the sustainable management of natural resources and nature protection are growing in importance as long-term challenges, along with climate change adaptation. The note aims to offer guidance on how the forest resource can continue to provide environmental goods and services while supporting both forest villages and the wood processing sector in a sustainable and cost efficient manner into the future. Turkey's natural resources face increasing pressures from growth in energy use, industry, transport, tourism, and agriculture resulting in water stress, soil erosion and pollution. Turkey is already addressing a range of regulatory and institutional reforms in the environment and forestry sectors and prioritizing investment programs in infrastructure, pollution mitigation, and afforestation. Measures to address these challenges are now becoming a priority for the Government. This Forest Policy Note (FPN) builds on previous work within the forestry sector. It aims to inform the World Bank project formulation process and the forestry sector by reviewing the sector and highlighting the main policy issues and identifying possible actions. This study will assist in identifying and designing investment opportunities within the sector. It is not a forest policy per se, although it could serve as an input to a forest policy formulation process.